2017
DOI: 10.1007/s00381-017-3499-6
|View full text |Cite
|
Sign up to set email alerts
|

Superselective transvenous embolization with Onyx and n-BCA for vein of Galen aneurysmal malformations with restricted transarterial access: safety, efficacy, and technical aspects

Abstract: TVE with liquid embolic agents is a safe and effective salvage method for VGAMs with restricted transarterial access, previously considered as poor candidates for endovascular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…To our knowledge, no treatment of mural type VAGM with WEB devices has been reported before. Liquid embolic agents—traditionally cyanoacrylate5 and, more recently, precipitating agents such as Onyx6—are well suited for choroidal type VGAM. In choroidal type malformations, a combined transarterial and transvenous approach is necessary 1 4 7–9.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no treatment of mural type VAGM with WEB devices has been reported before. Liquid embolic agents—traditionally cyanoacrylate5 and, more recently, precipitating agents such as Onyx6—are well suited for choroidal type VGAM. In choroidal type malformations, a combined transarterial and transvenous approach is necessary 1 4 7–9.…”
Section: Discussionmentioning
confidence: 99%
“…Transvenous access (TVA) has diagnostic and therapeutic utility in neuroendovascular surgery, ranging from diagnostic venography and venous sampling to transvenous embolization, thrombectomy, and stenting. TVA is considered the route of choice for the treatment of a wide range of neuroendovascular conditions that include, but are not limited to, inferior petrosal sinus sampling, mechanical thrombectomy in cerebral venous sinus thrombosis, venous stenting for idiopathic intracranial hypertension, and embolization of vein of Galen malformations, dural arteriovenous fistula, and carotid–cavernous fistula 78–87…”
Section: Transvenous Accessmentioning
confidence: 99%
“…In previous literature, it was considered to be not feasible due to increased morbidity. In recent article, Orlov et al 48 considered it was a safe and effective salvage method for VGAM with restricted transarterial access. Besides, Meila et al 49 described a combined transvenous and transarterial approach, called kissing microcatheter technique.…”
Section: Endovascular Therapymentioning
confidence: 99%
“…In mural type, NBCA is a preferred embolic material due to the properties of quick precipitation and adhesion to vessel. 48 In addition, Joo et al 42 first reported a patient with a mural-type VGAM who was successfully treated using the Micro Vascular Plug system, which may be a potential available option.…”
Section: Endovascular Therapymentioning
confidence: 99%